Integration of holistic education with pre-service teacher cultivation: dimensional analysis and role perceptions - Muhamad, Mohd Mokhtar; Mustakim, Siti Salina; Zhao, Yanmei; Yang, Zhufen (Pakistan Journal of Social Sciences (PJSS), 2024)
Purpose: The study aims to explore the integration of holistic education principles with pre-service teacher (PST) education, focusing on the significant impact of holistic education on students' comprehensive development and the contrast between holistic teachers and traditional teaching roles to improve PST education. Methodology: Through a literature review method, the research systematically reviews and synthesizes existing literature on holistic education and its integration with PST education, building a comprehensive understanding of the core dimensions of holistic education and the multifaceted roles of holistic teachers. Findings: The research identifies five core dimensions of holistic education: intelligence and cognition, physical and mental health, socio-emotional, ethical and moral, and spiritual cultivation. It highlights the multiple roles of holistic teachers, such as life mentors, project collaborators, emotional supporters, and learning partners, emphasizing their unique value in promoting students' comprehensive development. Implications: The study underscores the urgent need to integrate holistic education principles into PST education to prepare future educators capable of meeting both the academic and comprehensive developmental needs of students. By advocating for the cultivation of future holistic teachers, the research offers valuable insights into educational reform, aiming to provide K-12 students with a richer, more balanced, and meaningful educational experience.